2023
DOI: 10.1063/5.0156349
|View full text |Cite
|
Sign up to set email alerts
|

Analytical theory for a droplet squeezing through a circular pore in creeping flows under constant pressures

Zhengxin Tang,
François Yaya,
Ethan Sun
et al.

Abstract: We derived equations and closed-form solutions of transit time for a viscous droplet squeezing through a small circular pore with a finite length at microscale under constant pressures. Our analyses were motivated by the vital processes of biological cells squeezing through small pores in blood vessels and sinusoids and droplets squeezing through pores in microfluidics. First, we derived ordinary differential equations (ODEs) of a droplet squeezing through a circular pore by combining Sampson flow, Poiseuille … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Instead, the external fluid forms a lubrication layer between the droplet and each wall as shown in Figure 2, where h is the thickness of each layer. For a 2D droplet in a Hele-Shaw flow in a channel, it was shown that h is related to the channel height T and to the capillary number Ca as: Like the Sampson term shown in our previous work [5], the Roscoe term can be split into two terms of two half problems (the last two terms in Equation ( 14)). Equations ( 7) and ( 14) can be solved for 𝑉 and 𝑉 .…”
Section: Relationships Between Pressure Drop and Lubrication Layer Ve...mentioning
confidence: 87%
See 4 more Smart Citations
“…Instead, the external fluid forms a lubrication layer between the droplet and each wall as shown in Figure 2, where h is the thickness of each layer. For a 2D droplet in a Hele-Shaw flow in a channel, it was shown that h is related to the channel height T and to the capillary number Ca as: Like the Sampson term shown in our previous work [5], the Roscoe term can be split into two terms of two half problems (the last two terms in Equation ( 14)). Equations ( 7) and ( 14) can be solved for 𝑉 and 𝑉 .…”
Section: Relationships Between Pressure Drop and Lubrication Layer Ve...mentioning
confidence: 87%
“…Here, we determine the durations of the droplet transit stages and of its total transit through the slit, based on the pressure drops calculated above. To do so, we adapted the procedures used in the circular pore case [5]. For stages I and V, the time needed for the droplet to form or retract a curved half-ellipsoidal shaped droplet head is very small, and so they are considered negligible for this study.…”
Section: Transit Timesmentioning
confidence: 99%
See 3 more Smart Citations